Formation Mechanism of Cu-based Ohmic Contacts for GaAs Solar Cells - Liu,M; Soeriyadi,AH; Song,N; Hsiao,PC; Romer,U; Ekins-Daukes,N; Lennon,A (2020)
Copper contacts on GaAs are gaining increasing attention for low-cost high-efficiency solar cell devices. Cu/Ge/Pd and Cu/Pt/Ti/Pt contacts have been reported to achieve low specific contact resistivities in the range of 10_{-5}\ Ω \text{cm}_{2}. A preliminary study for the formation mechanism of these two Cu-based structures on both n-type and p-type GaAs substrates subjected to different thermal annealing conditions is reported. The results indicate that the formation of the Cu3Ge and PdGaxAsy compounds in conjunction with the creation of Ga vacancies are among the reasons for low contact resistance for n-GaAs. The high work function of Pt and high melting temperature of both Pt and Ti help to reduce the contact resistance for p-GaAs.